The Use of Herbal Medicine in Children of Birjand City, Iran - Azita Fesharakinia (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2015)
Background and Objectives: In recent years, the use of herbal medicine is increasing in different countries of the world. In this study, the use of herbal medicine in children and its related factors were investigated in Birjand city.